Kontribusi Pemikiran Ibnu Sina dan Relevansinya dengan Pendidikan Islam di Era Modern - Muhammad Habibirrahim; Misra Misra (Jurnal Budi Pekerti Agama Islam, 2025)
Ibn Sina (Avicenna), a 10th-century Muslim philosopher, scientist, and educator, has made major contributions to Islamic educational thought. This paper aims to examine the relevance of Ibn Sina's educational thought in the context of modern Islamic educational philosophy. Through a qualitative approach with literature study, this article analyzes Ibn Sina's ideas on the goals of education, stages of child development, and learning methods, as well as their relationship to the challenges of contemporary Islamic education. The results of the study show that Ibn Sina's thoughts are not only philosophical but also applicable, and remain relevant in efforts to build a holistic and sustainable Islamic education system.